Current understanding of multi-country human monkeypox outbreak: a narrative review - Vas, Geoffrey (International Journal of Research in Dermatology, 2022)
Outbreaks of infectious diseases have occurred throughout history. They appear to be increasing in frequency, particularly because of the increasing emergence of viral diseases from animals. Monkeypox is a zoonotic orthopoxviral, similar to smallpox, although with lower mortality. Cases of human monkeypox are rarely seen outside of west and central Africa. The current outbreak is the first of its kind where the transmission is reported in Europe without known links to Africa. India reported the first case of monkeypox from the Southeast Asia region in the state of Kerala, on July 14, 2022. India till now (August 2022) has reported nine monkeypox cases and one death owing to the viral zoonosis infection. It causes flu-like symptoms such as fever, chills, and rash, usually mild, and most patients recover without therapy. As with most viral illnesses, the treatment’s mainstay of clinical management for a typical monkeypox infection is supportive symptom management. Acting quickly and proactively, focusing on building surveillance, promptly identifying monkeypox infection, and implementing preventive measures will be vital for containing this pandemic.